IPRs, creative economies and localized development initiatives - Alexander Puutio (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
Creativity and innovation play increasingly important roles in modern societies. In both developed and developing countries alike, artistic, scientific and economic creativity accounts for significant portions of GPD and trade in creative goods is an increasingly important contributor to global trade flows. Regardless of the importance of creativity and innovation to our economies, the concept of creative economies remains somewhat underdeveloped and underutilized, largely due to difficulties in coming to consensus with regards to which behaviors, economic activities and resulting industries to include. This paper has examined the connections between local creative economies and IPRs regimes and we propose that creative economies are defined as comprising of the primary results of artistic, scientific and economic creativity that fall under the protection of main types of IPRs such as patents, trademarks and copyrights. From this new vantage point, this paper notes that local administrations and policymakers have various localized development intervention instruments that can promote creative economies at their disposal. Of these instruments, the One Village One Product movement, which originated from Japan's Oita prefecture stands out as a particularly robust project framework for promoting local creative economies. This paper also provided an assessment of the objectives, methodologies and applications of the movement across numerous countries and it showed that OVOP programmes have been successfully implemented in a variety of settings. With localized product development and export promotion at its heart, the OVOP programme has proven to be particularly flexible and adaptable to a wide range of policy objectives - ranging from rural poverty alleviation to brand agriculture and SME development - and operational settings with both developed to developing economies findings success under the OVOP movement. The paper concludes with an in-depth assessment of the UNIDO, Thai, Malawi and Nepalese models of OVOP implementation. These models and examples of direct application are presented to local administrators and policymakers as guidance and inspiration of how OVOP programmes can be implemented in support of creative economies.
Keywords: K33; L52; L3; 330; Creative economies; Intellectual Property Rights; Local Economic Development; Rural Development